2017
DOI: 10.3390/rs9121292
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Use of Sentinel-1 and Sentinel-2 Images for Operational Soil Moisture Mapping at High Spatial Resolution over Agricultural Areas

Abstract: Abstract:Soil moisture mapping at a high spatial resolution is very important for several applications in hydrology, agriculture and risk assessment. With the arrival of the free Sentinel data at high spatial and temporal resolutions, the development of soil moisture products that can better meet the needs of users is now possible. In this context, the main objective of the present paper is to develop an operational approach for soil moisture mapping in agricultural areas at a high spatial resolution over bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
255
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(266 citation statements)
references
References 70 publications
(108 reference statements)
7
255
0
4
Order By: Relevance
“…This approach consisted of applying two networks one after the other, the first to estimate soil moisture and the second to estimate soil roughness. El Hajj et al [19] showed that the use of VV alone provides better soil moisture estimation in comparison with the use of VH alone or the use of VV and VH together. Accordingly, only the VV polarization was used in this study for estimating soil parameters.…”
Section: Methodological Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach consisted of applying two networks one after the other, the first to estimate soil moisture and the second to estimate soil roughness. El Hajj et al [19] showed that the use of VV alone provides better soil moisture estimation in comparison with the use of VH alone or the use of VV and VH together. Accordingly, only the VV polarization was used in this study for estimating soil parameters.…”
Section: Methodological Overviewmentioning
confidence: 99%
“…In El Hajj et al [19], VV polarization provides better results in comparison to VH alone or to the use of VV and VH together. Only the results corresponding to VV are therefore presented.…”
Section: Estimation Of MVmentioning
confidence: 99%
See 1 more Smart Citation
“…Several satellite missions and instruments including SMOS (Soil Moisture and Ocean Salinity) [7,8], SMAP (Soil moisture Active and Passive) [9], and ASCAT (Advanced Scatterometer) [10] provide SSM estimates at coarse spatial resolution and very high revisit time (up to 1 day). Recently, SSM maps at very high spatial resolution (up to plot scale) and high revisit time (6 days) derived from Sentinel-1 (S1) satellite were provided for the Occitanie region in the southern part of France [11].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic aperture radar (SAR) and optic data fusion is one of the most widely used approaches [28][29][30][31]. The integration of data acquired by optical sensors and SAR data may provide useful information for reducing ambiguity due to the presence of vegetation.…”
Section: Introductionmentioning
confidence: 99%